(untitled) (Tempo e Argumento, 2021)
This article discusses some senses produced in the research experience and production of a documentary about territory memories where was founded Oscar Schneider Municipal Alienated People Shelter (1923-1942), Joinville’s first psychiatric institution. The shelter edification was realized, in second decade of twentieth century, at the bottom of a cemetery territory and far from urban center contact. After its closure, the physical structure was used as Politic Prison (1942-1945) and, later, as military police families habitation (1950-1970), until it was demolished, around 1970, in order to expand the cemetery. In this article, it is narrated the script elaboration and the “Invisible Memories” documentary recording process, constituted by interviews with witnesses of the mansion existence and aesthetic-artistic interventions (performances and images projections) operated in actual territory where existed the municipal cemetery edification. The article presents as results reflexions about ethical relation with lives traces that passed by the psychiatric institution and also points to political importance of invisibilized memories tensioning strategies connected to madness history. Keywords: Madness History; madness; memory; Oscar Schneider Municipal Alienated People Shelter.